Adjuvanted Recombinant Glycoprotein E Herpes Zoster Vaccine. (16th October 2019) - Levin, Myron J; Weinberg, Adriana
Abstract: The adjuvanted recombinant glycoprotein E herpes zoster (HZ) vaccine is superior to the live attenuated HZ vaccine, with an efficacy >90% against HZ in healthy immunocompetent adults aged ≥50 years after vaccination. In pivotal studies, the efficacy of the new vaccine varied very little with the age of the vaccinee and decreased only by 5–10% in the 3.5 years after immunization. This nonlive vaccine was successfully administered to small cohorts of immunocompromised individuals; initial trials showed efficacy of >60–80% in several such settings. Potential drawbacks include the requirement for 2 vaccine doses separated by 2–6 months, local and systemic reactogenicity that is significantly greater than observed with commonly used vaccines, and the inclusion of a strong adjuvant that has been minimally studied in clinical settings where it might be problematic, such as in people with autoimmune diseases. Postmarketing studies are underway to address some of the drawbacks. Abstract : The adjuvanted recombinant zoster vaccine is more effective than the live zoster vaccine, but more reactogenic. Efficacy declines minimally with increasing age of immunocompetent vaccines. Protection is maintained for ≥4 years. It is likely to be effective in people with many immunocompromising conditions.